Quranic Perspective on Leadership in Educational Institutions - Zain Sarnoto, Ahmad; Rahmawati, Sri Tuti (The International Journal of Education Management and Sociology, 2022)
This study examines leadership in educational institutions from the perspective of the Qur'an. As a guide to the life of Muslims, of course the Qur'an has a broad perspective, not only about worship but also about leadership. This type of research is library research. The approach used is an organizational approach. The theory used is the theory of leadership. The findings in this study are: first, leadership in educational institutions according to the Qur'an is contextual, complex, and flexible, between transactional, transformative, and serving leadership. Such leadership is worth fardhu kifayah in the rule of Islamic law. Second, the framework of leadership and organizational behavior in educational institutions according to the perspective of the Qur’an is more appropriate to be called Neo-Institutionalism. where leadership is influenced by the teachings and values ​​of Islamic beliefs. The practice of leadership in educational institutions is more accurately called the realization of and manifestation of the verses of the Qur’an. While the teachings of the Qur’an, according to the scholars of interpretation, are very professional in assessing the work. The contribution of this research is an offer of discourse in the form of an opinion that the leadership practice shown by Islamic-based organizations is part of the worship of Muslims in carrying out religious teachings.